Analisis Faktor Teknis dan Non Teknis Keberhasilan Inseminasi Buatan pada Kawasan Sentra Ternak Sapi di Kabupaten Tebo - Fachroerrozi Hoesni; Firmansyah Firmansyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The success of artificial insemination (IB) in the central area of beef cattle in the Tebo based on technical or non technical indicators are still not satisfactory. To increase the success of the IB to do an analysis of the determinants of the success of the IB in terms of technical factors, as well as non technical factors. The purpose of this research is to analyze the keragaan success rate of IB, and to analyze the effect of technical and non technical factor towards the success of the IB on beef cattle in the central area of Bali cattle in the Tebo. Research methods used in this research is a survey and laboratory techniques, with the withdrawal of sample Cluster Random Sampling that is the central area of beef cattle in the Tebo. The sample size in this study were determined by using the iterati method. Measuring qualitative variables used questionnaire form questions with Scala Likert's Summated Rating's. Validity or kesakhihan research results is determined by measuring instrument which is used i.e. testing the validity of a test (test of validity) and reliability (reliability test of) instruments. The scale of measurement data obtained are ordinal scale that is varied and the ratio. For the ordinal scale of research data done transformation into interval scale using Method of Succesive Interval (MSI). To analyze the effect of the hormone content of inseminator, skills and mineral feed, body condition score and motility of the sperm toward the success rate of artificial insemination in cattle at Tebo Regency in the used path analysis (path analysis).